Scaling Software-Defined Networks for AI-Powered Cloud Services - Singh, Shireesh Kumar (International Journal of Computing and Engineering, 2025)
The exponential growth of artificial intelligence (AI) and machine learning (ML) has significantly transformed the requirements for cloud infrastructure, demanding advanced networking solutions capable of handling the unique challenges posed by AI workloads. Traditional networking systems fall short when dealing with the bursty traffic patterns, extreme latency sensitivity, and massive data throughput needed for modern AI operations. Software-defined networking (SDN) offers a crucial solution by providing flexible, programmable, and dynamically scalable network infrastructure. This guide outlines four core pillars necessary for AI-ready network architectures: automation, performance optimization, resilience, and security. Automation spans the entire network lifecycle, including infrastructure provisioning, virtual network configuration, rapid regional deployment, and consistent configuration management through distributed state systems. Performance optimization involves leveraging AI for network path tuning, hardware acceleration with specialized units like SmartNICs and FPGAs, kernel bypass techniques for software modules, and dynamic latency-throughput balancing. Resilience mechanisms focus on device discovery, self-healing agents, redundant traffic paths, and automated troubleshooting. Security measures emphasize identity-based authentication, microsegmentation, modern protocol support (e.g., IPv6), regulatory compliance through automated audits, and advanced threat detection using behavioral algorithms. The integration of zero-trust principles within cloud-native architectures ensures robust security while maintaining optimal performance. This guide provides actionable strategies based on real-world deployments, combining theoretical concepts with practical insights for building scalable, high-performance AI cloud services, essential for organizations aiming to stay competitive in the evolving AI landscape.